HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP DETEKSI DINI KANKER SERVIKS DENGAN PEMERIKSAAN IVA DI PUSKESMAS SEKUPANG - Suratin Suratin; Susanti Susanti (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2017)
One of the most possible ways of early detection for cervical cancer is through theVIA examination. This study aims to determine the correlation of knowledge levels and attitude of adult female on early detection for cervical cancer with VIAtest.This research is an analytical survey study with cross sectional approach. The population investigated isthe fertile age couples attended the Sekupang Health Centre dated from June to July 2017. Furtherfrom the population, 71 respondents were selected as the sample through accidental sampling technique. This research utilizes questionnaires to collect the data, then analyzed by chi square statistical test. The result presents that74.6% female adults have good knowledge level, 64.8% of them show negative attitude, and 64.8% women do not perform the VIA test.The correlation coefficients obtained for the knowledge is p = 0.000 and attitude is p = 0.010 (p<0.05). These findings verified that there is a significant correlation between knowledge levels and attitude of adult women on early detection of cervical cancer by performing the VIA test, particularly at Sekupang Public Health Center in 2017. Finally, it is suggested for health workersof Sekupang Health Center to develop a more intensive and innovative counseling program on the cervical cancer as well as on how to detect the early sign of the cancers in women for general